BL Lacertae: Recovering intrinsic Trajectory of a Quasi-Stationary Jet Feature on Subparsec-Scales - Hambardzumyan, L. A.; Arshakian, T. G.; Pushkarev, A. B.
Very Long Baseline Array (VLBA) observations allow us to investigate the fine structure and dynamics of the inner part of the BL Lacertae jet. Long-term VLBA monitoring at 15 GHz has revealed the existence of a quasi-stationary component (QSC) in the jet interior, located about 0.26 mas from the radio core, followed by superluminal moving radio components. The study of the QSC motion is important in order to shed light on the dynamics of the inner part of the relativistic jet on spatial scales of milliparsecs. The latter is problematic due to measurement errors on such scales. In addition, the apparent QSC motion is a combination of the intrinsic motion of the QSC and the radio core, which predominantly occurs in the direction of the jet axis. Careful error analyses and apparent trajectory smoothing techniques are important to reveal the QSC intrinsic motion. We use 164 epochs of VLBA monitoring of the jet in BL Lacertae, available as part of the MOJAVE program, to study the QSC motion. We apply a moving average method to filter out the core contribution, which allows the detection of QSC intrinsic motion and develop an algorithm to clean up the smoothed trajectory using QSC positioning errors. We find that the QSC intrinsic trajectory is a combination of irregular reversals occurring on scales from about 0.15 yr to 0.5 yr. An analysis of the estimates of the reversal characteristics is presented for smoothed and cleaned trajectorie
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture